An experimental study of the flow characteristics and velocity fields in an operating room with laminar airflow ventilation. (May 2020) - Lin, Tee; Zargar, Omid Ali; Lin, Kuan-Yu; Juiña, Oscar; Sabusap, Dexter Lyndon; Hu, Shih-Cheng; Leggett, Graham
Abstract: A critical aspect of the role of ventilation in hospital operating rooms (ORs) is the prevention of surgical site infection (SSI) which is largely attributable to airborne infection. Ventilation using clean filtered air is the primary means of airborne infection control. Many modern OR ventilation systems use laminar airflow (LAF) for air distribution. Conventional LAF ventilation supplies air directly over the surgical area which creates a sterile zone and uses wall-mounted air returns located at low level. A problem avoided with this design is the formation of recirculation in the non-sterile zone which arises due to disruption of LAF. This recirculation can lead to entrainment of the contaminated room air to the supply airflow which can increase the risk of SSI. In order to prevent this entrainment, airflow in the non-sterile zone has to be significantly altered. In this study, the application of ceiling returns and skirts in order to prevent the recirculation is experimentally investigated. Airflow patterns were analyzed using smoke flow visualization and particle image velocimetry (PIV). A novel laser sheet generator was used for illumination of the smoke particles. The effects of the supply flow rate, skirt length, and percentage of ceiling-return flow rate on the recirculation were assessed using Taguchi method. The results show that the application of ceiling return can eliminate the recirculation. Ceiling-return flow rate has the greatest influence, followed by the supply flow rate and the skirt. The findings of this study could contribute to the improvement of the conventional LAF ventilation design. Highlights: The application of ceiling return can eliminate the recirculation in the non-sterile zone. Increasing the ceiling-return flow rate drastically reduces the recirculation vortex size. Long skirt can significantly prevent the shortcutting of the supply air into the ceiling return. A long skirt coupled with high supply flow rate can induce recirculation.